BIOREMEDIATION OF ACID MINE DRAINAGE FROM COAL MINING AT LABORATORY SCALE USING Citrobacter youngae AND Aspergillus niger - NURUL RIZKI (NIM: 22111004), INTAN
Acid mine drainage (AMD) is produced in mining activities as containing- sulfideminerals exposed to air and oxidized within spesific rate. Previous research on AMD focused on physical and chemical treatment (remediation). This research aims to study biological treatment of AMD using Citrobacter youngae and Aspergillus niger, and mixture between them, also to measure the optimal time to conduct bioremediation based on several parameters. AMD sample was taken from PT. Berau Coal Ã‚Â– East Kalimantan. Bioremediation process was performed at laboratory scale during 8 weeks within weekly sampling. The amount of inoculum for each treatment was 10% v/v. Some parameters observed pH, Fe concentration, Mn concentration, sulphate (SO4 2-) concentration, Fluorescein Diacetate Assay (FDA) and precipitation product. Treatment C (using bacteria), pH solution increased significantly right after the inoculation of bacteria at pH 5.9 then increased into neutral at pH 7.35 after a week of incubation; the removal range of dissolved Fe was between 86-97%; the removal range of dissolved Mn was between 47-93%; the lowest SO4 2- concentration was at 63.79 mg/L. Treatment As (using fungi with aeration), pH solution increased significantly on the 4th week of incubation at pH 6.6 then stabilized until the last week at pH 6.5; the removal range of dissolved Fe was between 12-34%; the removal range of dissolved Mn was between 54-96%; the lowest SO4 2- concentration was at 68.44 mg/L. Treatment At (using fungi without aeration), pH solution was stable at 6; the removal range of dissolved Fe was between 2-16%; the removal range of dissolved Mn was between 49-87%; the lowest SO4 2- concentration was at 89.72 mg/L. Treatment M (mixture of bacteria and fungi), pH solution was stable on the 4th week at pH 8.5; the removal range of dissolved Fe was between 18-38%; the removal range of dissolved Mn was between 50-90%; the lowest SO4 2- concentration was at 60.77 mg/L. FDA assay showed that microorganisms in each treatment were alive and metabolically active during the bioremediation process. The precipitation end product characterized by XRD was identified as calcian, ordere [(Na,Ca)Al(Si,Al)3O8]; podium calcium sulfate [Na4Ca(SO4)3]; tridymite [SiO2]; hematite [Fe2O3]. From the above, it can be concluded that remediation using bacteria was the best complies treatment based on coal mining wastewater standard, and the optimal time for remediation process was approximately 4 weeks.